ALEMTUZUMAB IMPROVES EDSS FUNCTIONAL SYSTEMS SCORES IN RRMS. Issue 12 (15th November 2016) - Giovannoni, Gavin; Berkovich, Regina; Fernandez, Oscar; Wiendl, Heinz; Margolin, David; Thangavelu, Karthinathan; LaGanke, Christopher
Abstract : In patients with relapsing-remitting MS (RRMS) and an inadequate response (≥1 relapse) to prior therapy, alemtuzumab improved Expanded Disability Status Scale (EDSS) functional systems scores (FSS) over 2 years versus subcutaneous interferon beta-1a (CARE-MS II; NCT00548405 ). Here we assess alemtuzumab's effect on FSS over 5 years. Patients received alemtuzumab at baseline and Month 12 in the core study. Patients entering an extension (NCT00930553 ) could receive as-needed alemtuzumab retreatment, or another disease-modifying therapy (DMT), for disease activity. EDSS was evaluated quarterly by blinded raters. 6-month confirmed FSS disability progression was defined as ≥1.0-point increase in an FSS. 393 (93%) alemtuzumab patients entered the extension; 357 (91%) remained on study through 5 years, 60% received no alemtuzumab after Month 12, and 92% received no other DMT. Over 5 years, mean cerebellar, pyramidal, sensory, and cerebral FSS did not exceed baseline; for each FSS, 71%–80% of patients were free from disability progression. Patients who received only 2 courses of alemtuzumab and no other DMT for 5 years generally had lower FSS than other patients. RRMS patients with inadequate response to prior therapy had persistent improvement/stability across multiple FSS over 5 years with alemtuzumab; most patients received no additional treatment since Month 12. Study supported by Sanofi Genzyme and Bayer Healthcare Pharmaceuticals.